Pelatihan Dewan Kemakmuran Masjid dengan Pengembangan Bisnis Online - Andriyansah, Andriyansah; Wihadanto, Ake; Geraldina, Ira; Febrianti, Rini; Paramitha, Diky; Nataliani, Nadya Putri (Gandhi: Jurnal Pengabdian Kepada Masyarakat, 2024)
Training of the Mosque Prosperity Council (DKM) with a focus on online business development. This activity aims to equip DKM administrators to develop business units for economic independence in running online businesses and their impact on the welfare of the people. the research was conducted online by involving administrators from the Al-Amanah Kujang Mosque DKM. The research was conducted online by involving administrators from Al-Amanah Kujang Mosque, Jl. Tongkeng Dalam No. 48 Merdeka Sumur Bandung, including material on Digital-Based Indomie Warung Business Model, Use of Social Media to Increase Sales and Digital-Based Indomie Ramen Warung Financial Recording. The results showed a significant increase in the knowledge and skills of DKM administrators in running an online business after attending the training. Prior to the evaluation, the training participants were asked to create an Indomie-based online business unit based on products or services managed by the mosque. The online business is expected to provide additional income for the mosque that is used for DKM.DKM training on online business development is proven to be effective in empowering DKM administrators for economic independence and improving the welfare of the people. This approach can be applied more widely by considering the potential and characteristics of each mosque.